Implementasi Pancasila Dalam Memfilter Dampak Globalisasi dan Era Revolusi Industri 4.0 - Alexandria Sarah Vania; Dinie Anggraeni Dewi (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
This study to find out some the influences that arise as a result of globalization and industrial revolution4.0 can adversely affect the nationalism of a nation and also in the majority of the influence of globalization in the era of industrial revolution 4.0 can also cause a sense of nationalism towards a nation and the country becomes reduced or even lost. According to Yusuf Tri Herlambang (2018) The development of technology today is a phenomenon that essentially has a significant impact on all dimensions of life. The research method uses quantitative method or questionnaire where researchers give a number of questions and respondents answer the question. The result of this research is that globalization in the era of industrial revolution 4.0 is able to open the horizon or mindset of society globally or globally and have a positive or negative impact As for. Therefore, the role of Pancasila as the basis of indonesian ideology should be central. The role of Pancasila in efforts to filtrate the negative impacts arising from globalization must begin to be applied by the People of Indonesia through the application of the values contained therein in an effort to maintain the integrity of the indonesian people and nation.